1991
DOI: 10.3382/ps.0701499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Humidity During Incubation and Age After Hatch on Heat Tolerance of Neonatal Male and Female Chicks

Abstract: Effects of incubation 45 versus 55% relative humidity (RH) and early versus late hatching time on heat tolerance of neonatal male and female chicks were studied. Chicks were exposed for 48 h to temperatures of 35 (Experiment 1), 37 (Experiment 2), or 39 C (Experiment 3). Chicks that hatched from eggs incubated at 45% RH were lighter at hatch than chicks that hatched from eggs incubated at 55% RH. Chicks that hatched from eggs incubated at 55% RH lost more body weight and water during heat exposure than those t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
2
10
0
1
Order By: Relevance
“…Apart from that fat also influence the immune response of individuals. The respiratory quotient in hatching chicks in the range of 0.72-0.74 [ 10 ], indicating utilization principally of fat.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from that fat also influence the immune response of individuals. The respiratory quotient in hatching chicks in the range of 0.72-0.74 [ 10 ], indicating utilization principally of fat.…”
Section: Discussionmentioning
confidence: 99%
“…Hatching time was not affected by the percentage of relative humidity during incubation in this study. Hamdy et al (1991) showed that the body weight of chickens was 0.7 g higher when eggs were incubated at a relative humidity of 55% compared to 45%. Excess water is probably incorporated into the tissue of the chicken (Davis et al, 1988), but in studies by Hamdy et al (1991), Swann & Brake (1990b), and Bruzual et al (2000a), this extra water was rapidly lost after hatching.…”
Section: Incubation -Egg Weight Lossmentioning
confidence: 99%
“…Hamdy et al (1991) showed that the body weight of chickens was 0.7 g higher when eggs were incubated at a relative humidity of 55% compared to 45%. Excess water is probably incorporated into the tissue of the chicken (Davis et al, 1988), but in studies by Hamdy et al (1991), Swann & Brake (1990b), and Bruzual et al (2000a), this extra water was rapidly lost after hatching. As a result, no difference in body weight was observed at pull time (Bruzual et al, 2000a), and this suggests that the period and conditions between hatch and arrival at the farm affect hatchling quality more than the relative humidity during incubation.…”
Section: Incubation -Egg Weight Lossmentioning
confidence: 99%
See 2 more Smart Citations